Methylphenidate promotes the interaction between motor cortex facilitation and attention in healthy adults: A combined study using event‐related potentials and transcranial magnetic stimulation. Issue 12 (12th November 2018) - Berger, Christoph; Müller‐Godeffroy, Juliane; Marx, Ivo; Reis, Olaf; Buchmann, Johannes; Dück, Alexander
Abstract: Objective: This study investigated simultaneously the impact of methylphenidate (MPH) on the interaction of inhibitory and facilitative pathways in regions processing motor and cognitive functions. Method: Neural markers of attention and response control (event‐related potentials) and motor cortical excitability (transcranial magnetic stimulation) and their pharmacological modulation by MPH were measured simultaneously in a sample of healthy adults ( n  = 31) performing a cued choice reaction test. Results: Methylphenidate modulated attentional gating and response preparation processes (increased contingent negative variation) and response inhibition (increased nogo P3). N1, cue‐ and go‐P3 were not affected by MPH. Motor cortex facilitation, measured with long‐interval cortical facilitation, was increased under MPH in the nogo condition and was positively correlated with the P3 amplitude. Conclusion: Methylphenidate seems particularly to enhance response preparation processes. The MPH‐induced increased motor cortex facilitation during inhibitory task demands was accompanied by increased terminal response inhibition control, probably as a compensatory process. Abstract : Neural markers of attention and motor cortical excitability and their pharmacological modulation by MPH were measured simultaneously in healthy adults performing a cued choice reaction test. MPH induced an increase of motor cortex facilitation during inhibitory task demands, which was accompanied by increased terminal response inhibition control, probably as a compensatory process.